Peningkatan Daya Saing Umkm Di Kota Tasikmalaya Melalui Integrasi Msdm Dan Strategi Pemasaran Digital - Iwan Saputra; Siti Amirah Makarim; Lati Sari Dewi (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This community service activity aims to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Tasikmalaya City through the integration of Human Resource Management (HRM) and digital marketing strategies. MSMEs in Tasikmalaya City face various challenges, including low competitiveness, unstable income, traditional marketing issues, weak product branding, and limited financing. Through a participatory approach, this service analyzes the current state of MSME HRM and marketing, formulates an integrated model, and provides training and mentoring for implementing digital marketing strategies. The activities will be carried out from January to May 2026 in Tasikmalaya City. The expected outcomes include an increase in MSME actors' understanding and capacity in managing human resources and implementing digital marketing, which will ultimately contribute to enhancing MSME competitiveness and economic stability.